Digitalisasi Warisan Benda Bersejarah Pada Kawasan Pura Pucak Penulisan Menggunakan Metode Waterfall - Putu Wirayudi Aditama; Ni Komang Dani Juniantari; I Made Subrata Sandhiyasa; Ida Bagus Gede Sarasvananda; I Gede Iwan Sudipa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Sukawana Village has many temples and has a very interesting historical heritage so that it is used as one of the tourism sites, this village has a temple called Pura Pucak Penulisan which is located in Sukawana Village, this temple has many historical objects that have not been known by the surrounding community. The solution to overcome these problems is the digitization of historical objects in Pura Pucak Penulisan, Sukawana Village. The system development method uses the Waterfall method because it can provide a structured solution approach in producing a website as a medium for digitizing historical objects in the Pucak Penulisan temple area, Sukanawa Village. The implications of research with digitization can help the surrounding community and other people find information about historical objects in Pura Pucak Penulisan without having to see it directly to the place. Based on the results of research 103 respondents from the community regarding the digitization of historical objects in Pura Pucak Penulisan showed 98.1% with the digitization of historical objects in Pura Pucak Penulisan which provided clear information about the historical objects in Pura Pucak Penulisan, this was also supported by 21 respondents from the Sukawana Village Office showing 85% considered it important to digitize historical objects in Pura Pucak Penulisan, to maintain its cultural assets. And in the black-box testing results get the expected results with the appropriate test.